2009
DOI: 10.1007/s11255-009-9583-4
|View full text |Cite
|
Sign up to set email alerts
|

The comparative study of serum iron, copper, and zinc levels between bladder cancer patients and a control group

Abstract: In the present study, a relationship was seen between the level of trace elements and the occurrence of bladder cancer, suggesting that an increase in the serum level of Cu and a decrease in the levels of Zn and Fe might be important causes of bladder cancer occurrence; however, defining such a cause-and-effect relationship needs several prospective studies to be done, which seems necessary with regard to the high prevalence of this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 23 publications
13
46
0
1
Order By: Relevance
“…[27] Therefore, in patients with low serum levels of Mn, the antioxidant activity in the organs may be reduced and thus, these patients may become susceptible to various diseases. These findings were consistent with those reported by Mazdak et al [18] Mn deficiency leads to numerous disorders in humans such as bone deficiency, joint pain, diabetes, and dysmnesia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[27] Therefore, in patients with low serum levels of Mn, the antioxidant activity in the organs may be reduced and thus, these patients may become susceptible to various diseases. These findings were consistent with those reported by Mazdak et al [18] Mn deficiency leads to numerous disorders in humans such as bone deficiency, joint pain, diabetes, and dysmnesia.…”
Section: Discussionsupporting
confidence: 93%
“…[17] As shown in Table 2, serum levels of Zn were lower in the patient group than in the healthy group. Although these findings were consistent with those reported by Cobanoglu et al (2010), [11] Mazdak et al (2010), [18] and Cebi et al (2010), [10] they contradicted the findings reported for patients with malignant glioma by Arslan et al [19] Although Zn has the ability to stimulate collagen synthesis in osteoblasts and activate alkaline phosphatase, these processes have a crucial role in the mineralization and calcification of bones. [20] Zn deficiency is commonly associated with numerous disorders such as retarded bone growth.…”
Section: Discussionsupporting
confidence: 85%
“…It is reported that gastric cancer may be caused by reactive oxygen species (ROS), and dietary antioxidants, such as zinc, may protect against this disease (Wu et al, 2004;Mazdak et al, 2010). Superoxide dismutase (SOD) plays a key role in the detoxification of superoxide radicals.2).…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalar göstermiştir ki oksidatif strese bağlı hasarlanmalar kanserin gelişimindeki faktörlerden biri olabilir ve oksidasyonu azaltmak mesane kanserinin oluşumunu engelleyebilir (20). Bu durum antioksidant sistemi oluş-turan enzimlerin yapısında bulunan elementlerin oksidatif hasarın azaltılmasına katkı sağla-yabileceğini ve kansere karşı koruyucu bir etkilerinin olabileceğini düşündürtmektedir (21,22). Çinko oksidan-antioksidan özellikleri olan bir elementtir.…”
Section: Discussionunclassified